A Call to APSA Part 1: Learn about Community College Faculty. Issue 1 (1st January 2022) - Osorio, Maricruz Ariana; Parker, Sara; Richards, Erin
ABSTRACT: This article summarizes research on the profession of community college faculty generally and data gathered from a survey of political science faculty teaching at community colleges nationwide conducted in 2018. The purpose of the article is to educate the discipline about what life is like for faculty at two-year schools and specifically how political science faculty at these schools perceive their role.